Evaluation of Susceptibility of Asphalt Binders to Rutting through MSCR Test - Rong Chang; Aimin Sha; Pinxue Zhao; Songchang Huang; Cong Qi (Advances in Materials Science and Engineering)
Using modified asphalt binder is one of the most effective methods to solve the rutting problem of asphalt pavement, but the traditional G∗/sin  δ parameter is not enough to characterize the rutting resistance of modified asphalt in field use. In order to accurately evaluate the high temperature performance of asphalt and establish the relationship between the rutting resistance of binder and mixture, two kinds of matrix asphalt and three kinds of modified asphalt were selected for DSR and MSCR tests. G∗/sin  δ, nonrecoverable creep compliance Jnr, recovery rate R, and other parameters were used to characterize the permanent deformation resistance of the binder, and the correlation between these parameters and the results of rutting test was analyzed. The results show that Jnr3.2 can accurately characterize the permanent deformation resistance of asphalt, while the stress sensitivity index Jnrdiff is not applicable to all types of modified asphalt. In contrast, Jnrslope can better reflect the stress sensitivity of asphalt, and Jnrslope is significantly correlated with the results of rutting test.